دراسة وبائية سببية للطفوح الدوائية - السيد فاخر; رومية عبد الحليم; محمد ريم (Latakia University Journal -Medical Sciences Series, 2019)
تشكل الطفوح الدوائية مشاكل طبية، تشخيصية شائعة، وقد تكون شديدة لدرجة تودي بحياة المريض إذا لم تشخص باكراً. في دراستنا قمنا بحساب النسبة المئوية لمراجعي العيادة الجلدية في مشفى الأسد الجامعي والمصابين بالطفح الدوائي وكانت النتيجة 1.92 % . تضمنت الدراسة 200 مريض موزعين حسب نمط الطفح الدوائي إلى: 1 ـ اندفاعات طفحية 66 مريضاً. 2 ـ اندفاع دوائي ثابت 33 مريضاً. 3 ـ الطفوح الشرورية 49 مريضاً. 4 ـ الأنماط الأخرى 52 مريضاً. كما تم توزيعهم حسب الدواء المسبب إلى : 1 ـ المضادات الحيوية 119 مريضاً. 2 ـ خافضات الحرارة ـ مضادات الالتهاب 39 مريضاً. 3 ـ مضادات الاختلاج 18 مريضاً. 4 ـ الأدوية الأخرى 24 مريضاً. Adverse Drug Eruptions (ADE) are common medical problems, which may cause death if not diagnosed early. In our research, we found that 1.92 % of patients who come to the derma – clinic in AL- Assad Hospital had drug eruptions. The research included 200 patients distributed according to types of eruption as follows: 1 . 66 patients with exanthematous eruptions. 2 . 49 patients urticaria eruptions. 3 . 33 patients with fixed drug eruptions. 4 . 52 patients with Other types. Patients were distributed according to the causative drugs as follows: 1 . Antimicrobial: 119 patients. 2 . Antipyretic / anti-inflammatory: 39 patient. 3 . Anticonvulsants : 18 patient. 4 . Other drugs: 24 patient. Our research concluded that: The common types of ( ADE ) were Exanthematous eruptions, Urticaria eruptions, and then fixed drug eruptions. The most common causative drugs were antimicrobial, antipyretic / anti-inflammatory, and then anticonvulsants.